Creating better employment in agrifood systems: Where is more research needed? - Nguyen, Vi (International Food Policy Research Institute, 2023)
Agrifood systems represent a substantial source of employment for a diverse range of supply chain actors. In recent years, we have learned a lot from the rapid rise in innovations on what is needed to build more inclusive and sustainable agrifood systems that can lift people out of poverty and provide better job opportunities. Yet there are still critical gaps in knowledge to address before we get there.